Secretome of umbilical cord mesenchymal stem cells: Potential effects on melanoma - Fernandes, Pablo (2023)
Melanoma, a tumor resulting from the malignant transformation of melanocytes, is characterized by its aggressive nature and propensity to metastasize. Current treatment options for advanced melanoma are limited and mostly ineffective, highlighting the need for novel therapeutic approaches. Mesenchymal stem cells (MSCs) have increased considerable attention due to their anti-cancer and immunomodulatory properties. In particular, human umbilical cord MSCs (hUCMSCs) have shown promise in various therapeutic applications.